Comparative analysis of AI on human nutrition knowledge: Evaluating large language model-based conversational agents against dietetics students and the general population - Nicola Luigi Bragazzi; Stefania Monica; Federico Bergenti; Francesca Scazzina; Alice Rosi (PLoS ONE, 2025)
Understanding the core principles of nutrition is essential in the contemporary context of abundant and often contradictory dietary advice, to empower individuals to make informed dietary choices and manage diet-related non-communicable diseases. The role of Artificial Intelligence (AI) in providing nutritional information is increasingly prominent, but its reliability in this domain is not well-established yet. This study compares the nutrition knowledge of state-of-the-art Large Language Model (LLM)-based conversational agents and chatbots with that of human subjects having different levels of nutrition knowledge. The “General Nutrition Knowledge Questionnaire–Revised” (GNKQ-R) was administered to four LLMs (ChatGPT-3.5, ChatGPT-4, Google Bard, currently known as Google Gemini, and Microsoft Copilot), using zero-shot prompts. Responses were scored in accordance with the GNKQ-R’s guidelines. The average performance of AI systems across all LLMs was 77.3 ± 5.1 out of 88, comparable to that of dietetics students and significantly higher than English students. ChatGPT-4 scored highest among the LLMs (82/88), surpassing both groups of students (dietetics: 79.3/88, English: 67.7/88) as well as all other demographic groups. In “Dietary Recommendations”, ChatGPT-3.5 and ChatGPT-4 demonstrated comparable performance to dietetics students. ChatGPT-4 excelled in “Food Groups”, outperforming all human groups. In “Healthy Food Choices”, ChatGPT-4 achieved a perfect score, indicating a deep understanding of this subject. ChatGPT-3.5 excelled in “Diet, Disease and Weight Management”. Variations in the performances of the LLMs across different sections were observed, suggesting knowledge gaps in certain areas. Some of the tested LLMs, particularly ChatGPT-3.5 and ChatGPT-4, showed proficiency in nutrition knowledge, rivaling or even surpassing dietetics students in certain sections. This indicates their potential utility in nutritional guidance. However, this study also identified nuances and specific details where LLMs lack compared to specialized human education. The study highlights the potential of AI in public health and educational settings. However, LLMs may be limited in their capacity to generate personalized dietary advice that accounts for clinical complexity and individual variability, reinforcing the indispensable role of expert human judgment.